Evidence for Holocene centennial variability in sea ice cover based on IP25 biomarker reconstruction in the southern Kara Sea (Arctic Ocean). - Hörner, Tanja; Stein, Ruediger; Fahl, Kirsten (PANGAEA, 2017)
The Holocene is characterized by the late Holocene cooling trend as well as by internal short-term centennial fluctuations. As Arctic sea ice acts as a significant component (amplifier) within the climate system, investigating its past long- and short-term variability and controlling processes is beneficial for climate future predictions. This study presents the first biomarker-based (IP25 and PIP25) sea ice reconstruction from the Kara Sea (Core BP00-07/07), covering the last 8 ka. These biomarker proxies reflect conspicuous short-term sea ice variability during the last 6.5 ka that is identified unprecedentedly in the source region of Arctic sea ice by means of a direct sea ice indicator. Prominent peaks of extended sea ice cover occurred at ~3, ~2, ~1.3 and ~0.3 ka Spectral analysis of the IP25 record revealed ~400- and ~950-year cycles. These periodicities may be related to the Arctic/North Atlantic Oscillation (AO/NAO), but probably also to internal climate system fluctuations. This demonstrates that sea ice belongs to a complex system that more likely depends on multiple internal forcing.
Biomarker analyses on sediment core BP00-07/07 from the southern Kara Sea (Arctic Ocean)
Keywords: 2,6,10,14-Tetramethyl-7-(3-methylpent-4-enyl)pentadecane per unit mass total organic carbon; 2,6,10,14-Tetramethyl-7-(3-methylpent-4-enyl)pentadecane per unit sediment mass; 24-Ethylcholest-5-en-3beta-ol per unit mass total organic carbon; 24-Ethylcholest-5-en-3beta-ol per unit sediment mass; 24-Methylcholest-5-en-3beta-ol per unit mass total organic carbon; 24-Methylcholest-5-en-3beta-ol per unit sediment mass; 24-Methylcholesta-5,22E-dien-3beta-ol per unit mass total organic carbon; 24-Methylcholesta-5,22E-dien-3beta-ol per unit sediment mass; 4alpha,23,24-Trimethyl-5alpha-cholest-22E-en-3beta-ol per unit mass total organic carbon; 4alpha,23,24-Trimethyl-5alpha-cholest-22E-en-3beta-ol per unit sediment mass; Akademik Boris Petrov; AWI_Paleo; BP00; BP00-07/07; Carbon, organic, total; DEPTH, sediment/rock; Element analyser CHN, LECO CNS 2000; Gas chromatography - Mass spectrometry (GC-MS); GC; Gravity corer; Kara Sea; Paleoenvironmental Reconstructions from Marine Sediments @ AWI